Assessing long-term management options for the villages in the Korup National Park: an evaluation of all options - Diaw, C.; Tiani, A.M.; Jum, C.N.; Milol, A.; Wandji, D.N. (Cooperation Cameroun/Union Europeenne, WWF, CIFOR, 2003)
This study assesses the social, economical, ecological, political, legal, and institutional implications of options related to ‘resettlement’, ‘boundary change’, and ‘enclave’ delineation for each of the five park villages.The study finds that attempting to resettle all the villages from the Korup National Park (KNP) may not be realistic or achievable. At the same time, the present status quo proves not being tenable. Bareka-Batanga is the village the most clearly prepared to resettle, and the least costly too. If the Bakoko group of villages cannot be resettled, it will need a comprehensive development conservation plan within a ‘sustainable livelihood option’ here named ‘enclave option. Three options exist for Erat and its twin village Ekon I: resettlement, with the financial cost scenarios particularly high; maintaining them where they are presently, that implies the much lower short-term financial cost; changing of the park’s boundary.The economic analysis finds that under the original assumptions of the Korup project, resettling the villages remains a preferred option for long-term economic benefits. But slight changes into these assumptions significantly reduce forecasted benefits. By contrast, in the short term, the financial costs of resettlement are much higher than other options. The ecological assessment finds that people in the KNP are traditional forest-farmers, with almost 1/12th of the park already domesticated. At the same time, these communities depend vitally on the whole range of environmental services provided by the primary forest. In contrast, the study does not find evidence that hunting, fishing, or gathering by park villagers constitutes, as such, a threat to the sustainability of the wildlife or the ecosystems. The sociological analysis finds that communities’ perceptions of the KNP are dominated by the sentiment that they have been deceived and abandoned. Parts of these communities would still like to be resettled, other want to stop all talks of resettlement and just ‘divide’ up the forest between them and the Korup project. Legal alternatives to the resettlement such as degazettment of part of the KNP to allow for certain villages to stay where they are while exercising freely their activities; the adaptation of the management plan, with the justification that such enclaves fall within the fundamental objectives of the management of the park; and a special regulatory amendment, by Decree of the Prime Minister or by ordinance of the President of the Republic with regulatory power.